Pengembangan Media Game Petualangan Geomat Berbasis Adobe Flash untuk Meningkatkan Hasil Belajar Siswa Kelas 5 SD - Theo Hendratta Putra; Mawardi Mawardi (Universitas Kanjuruhan Malang, 2021)
The demands of 21st-century learning emphasize primary school teachers and students to have adequate skills, creativity, innovation following global dynamics. To meet the demands of 21st-century learning, the purpose of this study is to develop learning media for the game